PERDAGANGAN TERNAK DAN DAGING SAPI: REKONSILIASI KEBIJAKAN IMPOR DAN REVITALISASI PEMASARAN DOMESTIK (Forum Penelitian Agro Ekonomi, 2021)
For the last decade, average national consumption of beef increases by 4.5 percent/year, with a high trend of import i.e. 21.6 percent/year compared to that of domestic beef production rate of 2.6 percent/year. Development of beef cattle need long-term investment, therefore disincentive of import policy will give substantial impact, psychologically and economically, to the farmers. The objective of this paper is to formulate the harmonization of import policy and domestic marketing in order to support the development and sustainability of beef cattle agribusiness. In the context of the Food Law No.18/2012, the import policy of feeder cattle and beef cattle is the last resort policy and should be conducted with the principle of cautiously. Coordination and consolidation between the logistic institution (Bulog) and the importer association is needed in relation to implementation of price stabilization policy effectively and efficiently. The implementation of import policy based on price reference have to be conducted in conjunction with the powerful logistic system development. The respective policy should be complemented with the enhancement of domestic marketing efficiency for the benefits of increasing beef cattle population, beef production, and the welfare of the farmers. Policy direction of livestock and beef cattle domestic marketing is to maintain meat consumption diversification, deregulation of retribution and marketing system, enhancement of the institutional and bargaining position of the farmers, as well as gradual reducing of beef cattle inter-regional trade quota complemented with production development policy of beef cattle farming.
Keywords: beef cattle trade; import policy; domestic marketing; policy reconciliation